(untitled) (Global Scientific Review, 2025)
Any language is in a process of constant development and change. From this perspective, dialects, as living forms of language, also go through their own stages of development. Dialects of the Uzbek language have their own phonetic, lexical, and morphological characteristics in different regions. In particular, the dialects observed among the population living in the Kashkadarya region have a rich history and a complex linguistic system, and the assimilations in this region, that is, words that have come from other languages and their methods of formation, are one of the issues that deserve separate study. This article analyzes how words that have come from other languages are formed in the Uzbek dialects of the Kashkadarya region, the cases in which they have undergone phonetic, morphological, and semantic changes, and what language units participated in these processes.